An unusual case of Cardiobacterium valvarum causing aortic endograft infection and osteomyelitis - Eric G. Hauser; Imran Nizamuddin; Brett B. Yarusi; Karen M. Krueger (BMC, 2021)
Abstract Background HACEK (Haemophilus spp., Aggregatibacter spp., Cardiobacterium spp., Eikenella corrodens, and Kingella spp.) group organisms are responsible for 0.8% to 6% of all infective endocarditis cases, with Cardiobacterium spp. being the third most commonly implicated HACEK microorganism. Within this genus is Cardiobacterium valvarum (C. valvarum), a novel organism described in 2004. To date, only 15 cases of C. valvarum infection have been reported in the English-language literature, and have primarily been cases of infective endocarditis in patients with valvular disease. C. valvarum has not been reported to cause infections spreading to the surrounding bone. Case presentation We present a case of a 57-year-old man with a history of aortic dissection followed by aortic endograft replacement who presented with back pain. He was found to have radiographic evidence of an infected aortic endograft, along with vertebral osteomyelitis, discitis, and epidural phlegmon. Blood cultures identified C. valvarum as the causative organism. The patient was treated with ceftriaxone and surgical intervention was deferred due to the patient's complex anatomy. His course was complicated by septic cerebral emboli resulting in cerebrovascular accident. Conclusions This case report highlights C. valvarum, a rare and emerging HACEK group microorganism that warrants consideration in high-risk patients with evidence of subacute infection and disseminated disease. While C. valvarum classically presents as infective endocarditis, extra-cardiac manifestations have also been described. As demonstrated in this case, endograft involvement and osteomyelitis may occur in rare circumstances.